2020
DOI: 10.1021/jacs.0c02044
|View full text |Cite
|
Sign up to set email alerts
|

Structural Properties and Catalytic Implications of the SPASM Domain Iron–Sulfur Clusters in Methylorubrum extorquens PqqE

Abstract: Understanding the relationship between the metallocofactor and its protein environment is the key to uncovering the mechanism of metalloenzymes. PqqE, a radical S-adenosylmethionine enzyme in pyrroloquinoline quinone (PQQ) biosynthesis, contains three iron−sulfur cluster binding sites. Two auxiliary iron−sulfur cluster binding sites, designated as AuxI and AuxII, use distinctive ligands compared to other proteins in the family while their functions remain unclear. Here, we investigate the electronic properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 83 publications
2
22
0
Order By: Relevance
“…Elucidation of the catalytic function of auxiliary clusters in radical SAM enzymes in the SPASM-twitch family remains difficult. While reduction potentials of several other members of the SPASM-twitch family have been reported, ,,, ambiguity remains about their functions in catalysis due to the lack of understanding in the reduction potentials of reaction intermediates and the redox state of the auxiliary clusters during catalytic turnover. In this study, we used a combination of PFV, EPR, and DFT calculation to provide experimental evidence that the reduced 1+ state auxiliary cluster of MoaA reduces the aminyl radical intermediate to form the final product.…”
Section: Discussionmentioning
confidence: 99%
“…Elucidation of the catalytic function of auxiliary clusters in radical SAM enzymes in the SPASM-twitch family remains difficult. While reduction potentials of several other members of the SPASM-twitch family have been reported, ,,, ambiguity remains about their functions in catalysis due to the lack of understanding in the reduction potentials of reaction intermediates and the redox state of the auxiliary clusters during catalytic turnover. In this study, we used a combination of PFV, EPR, and DFT calculation to provide experimental evidence that the reduced 1+ state auxiliary cluster of MoaA reduces the aminyl radical intermediate to form the final product.…”
Section: Discussionmentioning
confidence: 99%
“…Like the ranthisynthase CteB, these enzymes share the canonical (β/α) 6 TIM barrel fold but differ in the nature of auxiliary iron–sulfur clusters. Whereas SuiB harbors in its C -terminal part a SPASM domain characterized by two auxiliary [4Fe-4S] clusters, it has been shown that PqqE contains one [2Fe-2S] and one [4Fe-4S] auxiliary clusters, with possible conversion of the [2Fe-2S] into a [4Fe-4S] cluster ( Zhu et al, 2020 ). In addition, one of the auxiliary clusters of PqqE is not coordinated by four cysteine residues, but by three cysteine residues and a conserved aspartate which likely modulates its redox properties ( Barr et al, 2018 ; Tao et al, 2019 ).…”
Section: Radical Sam Enzymes: An Emerging Superfamily Of Enzymesmentioning
confidence: 99%
“…Structural data shows that SkfB has an N-terminal RiPP recognition element (RRE) domain for peptide-binding. Subsequent is a classic partial (β/α) 6 barrel structure bounding the [4Fe-4S] cluster, and the C-terminal is a twitch domain harboring a [2Fe-2S] cluster, which is the same with the pyrroloquinoline quinone biosynthesis enzyme PqqE (Grell et al, 2018 ; Zhu et al, 2020 ). Unambiguously, SkfB catalyzes hydrogen abstraction from the α-carbon of Met12 of precursor peptide SkfA (Bruender and Bandarian, 2016 ).…”
Section: Biosynthesis Of Sactipeptidesmentioning
confidence: 99%